Editorial (Res Medica, 2014)
The first part of the sale of most of the Royal Medical Society’s Library at Sotheby’s has been promising. The suggested upper limit of £120,000 is now attainable if the next two sales follow the pattern of the first. This is gratifying for the people who had to make the decision about the best way to dispose of the books.It seems almost a paradox that the sale which was necessary for the Society to continue on a secure financial basis should, by realizing so much, have created a further dilemma. T h e problem can be simply stated as this: if the sale of the library produces a financial surplus over and above what is required for new premises and reasonable security for running those premises in the future, what is to be done with the surplus, or the interest from the investment?